The delivery of miR-21a-5p by extracellular vesicles induces microglial polarization via the STAT3 pathway following hypoxia-ischemia in neonatal mice - Dan-Qing Xin; Yi-Jing Zhao; Ting-Ting Li; Hong-Fei Ke; Cheng-Cheng Gai; Xiao-Fan Guo; Wen-Qiang Chen; De-Xiang Liu; Zhen Wang (Neural Regeneration Research, 2022)
Extracellular vesicles (EVs) from mesenchymal stromal cells (MSCs) have previously been shown to protect against brain injury caused by hypoxia-ischemia (HI). The neuroprotective effects have been found to relate to the anti-inflammatory effects of EVs. However, the underlying mechanisms have not previously been determined. In this study, we induced oxygen-glucose deprivation in BV-2 cells (a microglia cell line), which mimics HI in vitro, and found that treatment with MSCs-EVs increased the cell viability. The treatment was also found to reduce the expression of pro-inflammatory cytokines, induce the polarization of microglia towards the M2 phenotype, and suppress the phosphorylation of selective signal transducer and activator of transcription 3 (STAT3) in the microglia. These results were also obtained in vivo using neonatal mice with induced HI. We investigated the potential role of miR-21a-5p in mediating these effects, as it is the most highly expressed miRNA in MSCs-EVs and interacts with the STAT3 pathway. We found that treatment with MSCs-EVs increased the levels of miR-21a-5p in BV-2 cells, which had been lowered following oxygen-glucose deprivation. When the level of miR-21a-5p in the MSCs-EVs was reduced, the effects on microglial polarization and STAT3 phosphorylation were reduced, for both the in vitro and in vivo HI models. These results indicate that MSCs-EVs attenuate HI brain injury in neonatal mice by shuttling miR-21a-5p, which induces microglial M2 polarization by targeting STAT3.